Complete Mitogenomes of Deep-Sea Eels Histiobranchus bathybius and Simenchelys parasitica and a New Record of H. bathybius from the East Mariana Basin, Western Pacific Ocean - Jeonghoon Han; Han-Jun Kim; Byung-Jik Kim; Ji-Yeon Hyeon; Choong Hwan Noh; Young-Ung Choi (Journal of Marine Science and Engineering, 2024)
In this study, using Illumina sequencing, we sequenced first the complete mitochondrial genome (mitogenome) of two deep-sea eels, Histiobranchus bathybius and Simenchelys parasitica, collected from the East Mariana Basin in the Western Pacific Ocean. The complete length of the H. bathybius and S. parasitica mitogenomes were 16,696 and 16,687 bp, respectively, each containing 37 genes (13 protein-coding genes, 22 tRNA genes, and 2 ribosomal RNA genes). To enhance the accuracy of the identification of H. bathybius and S. parasitica, we performed a phylogenetic analysis of multiple deep-sea eels based on the mitochondrial DNA gene (cytochrome c oxidase subunit I [COI]) using the maximum likelihood method. Our phylogenetic tree analysis confirmed that the specimens collected in this study are congeneric species of H. bathybius and S. parasitica reported in previous studies. Based on these results, we report the first complete mitogenomes of H. bathybius and S. parasitica and a new record for the two species in the East Mariana Basin.